Government Responsibilities in Fulfilling Victims' Rights During the Rehabilitation and Reconstruction Phase After the Earthquake in Sulai Village, Ulumanda District, Majene Regency - Eka Dewi Kartika; Salma Laitupa (Musamus Law Review, 2022)
The rehabilitation and reconstruction phase is very important in restoring the environment, infrastructure, social, economic, cultural and psychological aspects of disaster victims, especially victims of the 6.2 magnitude earthquake in West Sulawesi in 2021. The rehabilitation and reconstruction phase is the stage where the community receives protection from the State in this regard. the central government and local governments in the recovery of all sectors of life after the disaster victims. 1 year after the earthquake in Sulai Village, Ulumanda District, it is still not evenly distributed to get the fulfillment of the facilities contained in the rehabilitation and reconstruction phase as a form of local government responsibility as stated in Article 5 of the Majene Regency Regulation No . 9 of 2019 concerning Disaster Management. areas. In the implementation of the rehabilitation and reconstruction phase in Sulai Village, there are 100% elements in the rehabilitation and reconstruction phase that have not been implemented at all, such as the implementation of security and order patrols, communication networks, community party activities, counseling by psychologists, reconciliation and conflict resolution, drainage development, health center repairs. Assistants, health counseling, counseling on disaster risk reduction efforts and permanent housing in the form of stimulant funds for earthquake victims have not been distributed evenly in Sulai Village.